Pop Up Media-Assisted Discovery Learning Model to Improve Elementary School Students' Collaboration Skills - Sesanti, Nyamik Rahayu; Ni'ama, Siti; Harini, Yuli Sri (Lucerna : Jurnal Riset Pendidikan dan Pembelajaran, 2025)
The low participation of students in group work, lack of ability to work together, and lack of mutual respect when completing joint tasks are problems in collaboration skills in grade IV of Bakalan Krajan 2 Public Elementary School, Malang City. This study aims to describe the application of the Discovery Learning learning model assisted by pop up interactive media in developing students' collaboration skills. The research subjects amounted to 29 students in grade IV, with data collected through observation using the rubric of assessment of collaboration skills, then analyzed quantitatively and qualitatively. The results showed an increase in students' collaboration skills by 21%, from an average of 58% in cycle I to 79% in cycle II. These findings show the potential effectiveness of the application of the Discovery Learning model assisted by pop up media in encouraging students to be more active, able to work together, and show mutual respect when completing group assignments. In addition to making a practical contribution to the development of invention-based learning practices in elementary schools, this study also adds references on the use of simple interactive media in improving collaboration skills. However, the results of this study are still limited to the context of one class and two learning cycles, so further studies with a wider scope of subjects, materials, and time are needed to test the sustainability of the impact of the intervention.